The importance of metacognition in physics problem solving: monitoring skills - Ali, Marlina (2015)
The purpose of this paper is to show the importance of metacognitive skills in solving force and motion problem. This study consists of 10 students and students were divided into 2 groups based on their test score. One group were classified as more successful (MS) problem solvers and the other one as less successful (LS) problem solvers. Students solved physics problems while talking aloud. Each of the students were videotaped. Interviews were conducted right after the test. Written answers from physics task were marked according to the schema. In this paper, findings from one question were discussed. The question called “lift’ problem. The thinking aloud were transcribed verbatim from the videotapes as well as interviews. Transcripts were coded and examined looking for both similarities and differences. As a conclusion, monitoring were shown as an important metacognitive skills in physics problem solving.